1985
DOI: 10.1161/01.cir.71.3.595
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of myocardial ischemia with proton magnetic resonance: effects of a three hour coronary occlusion with and without reperfusion.

Abstract: Proton (hydrogen-1) magnetic resonance imaging techniques have potential for the detection and characterization of changes associated with myocardial ischemia. Since image contrast is dependent on TI and T2 relaxation times, we examined these parameters in a canine preparation of occlusion of the left anterior descending coronary artery. Of 16 dogs studied, seven underwent 3 hr of coronary artery occlusion and nine underwent 3 hr of occlusion followed by 1 hr of reperfusion. After the dogs were killed, the hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
1

Year Published

1987
1987
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(14 citation statements)
references
References 12 publications
2
11
1
Order By: Relevance
“…Our results of transmural T2 signal abnormality in reperfused infarcts agree with those of Nilsson et al 24 but disagree with those of Johnston et al, 25 who found no significant change in epicardial T2 relaxation times after 3 hours of coronary occlusion with or without reperfusion. In a later report, however, Johnston and colleagues studied patients with acute reperfused MI and found that a high T2 signal was consistently transmural.…”
Section: Discussionsupporting
confidence: 67%
“…Our results of transmural T2 signal abnormality in reperfused infarcts agree with those of Nilsson et al 24 but disagree with those of Johnston et al, 25 who found no significant change in epicardial T2 relaxation times after 3 hours of coronary occlusion with or without reperfusion. In a later report, however, Johnston and colleagues studied patients with acute reperfused MI and found that a high T2 signal was consistently transmural.…”
Section: Discussionsupporting
confidence: 67%
“…In the study by Pflugfelder et al (2) infarct signal intensity was shown to increase from 5 f 24% (mean f standard deviation) before coronary occlusion to 116 & 100% after 3 to 4 h of occlusion. Such a large change in signal intensity would imply a much greater increase in T2 relaxation than was observed in our studies (3). Unfortunately, the study by Pflugfelder et al did not confirm their findings by measuring in vitro relaxation times in a spectrometer.…”
Section: Acute Myocardial Infarctioncontrasting
confidence: 64%
“…Although an increase in infarct signal intensity (compared to normal myocardium) could be readily appreciated in the excised heart imaged under optimal conditions, these changes were slight and difficult to appreciate in the beating heart. The increases in T, and T2 relaxation times as measured by spectrometer were small in both instances, with TI increasing by 10% and T2 increasing by 1 1% in one study (3). In the study by Pflugfelder et al (2) infarct signal intensity was shown to increase from 5 f 24% (mean f standard deviation) before coronary occlusion to 116 & 100% after 3 to 4 h of occlusion.…”
Section: Acute Myocardial Infarctionmentioning
confidence: 79%
“…Depending upon the duration of ischemia [150,152] edema in the infarcted myocardium prolongs the T1-and T2-relaxation time [151,153]. Differences in T1-relaxation may not be clinically useful for infarct detection unless paramagnetic contrast agents are administered (see below).…”
Section: Proton Relaxation Timesmentioning
confidence: 99%